Advances in the study of common bean resistance to bacterial diseases in Cuba. - Rodríguez, Odile; Faure, Benito; Benitez, Roberto; Carballo, Rita M.; Capote, Jeny (Agronomía Mesoamericana, 2015)
An experiment was carried out at the Lilliana Dimitrova Horticultural Research Institute in order to evaluate several advanced lines from the National Hybridization Program, and from the Nursery of Regional Resistance Sources of common bean, which were springled with Xanthomonas campestris (Xcp 530) – a highly aggressive bacterial strain. Fifteen varieties with intermediate resistance to the bacteria were selected. The CUT54, XAN 280, and 9356-26 lines were outstanding, showing better results than the control BAT 93.